Integrated Analysis of a Competing Endogenous RNA Network Reveals a Prognostic Signature in Kidney Renal Papillary Cell Carcinoma - He, Ruyi; Wang, Longyu; Li, Juan; Ma, Lixin; Wang, Fei; Wang, Yang (Frontiers in Cell and Developmental Biology, 2020)
The kidney renal papillary cell carcinoma (KIRP) is a relatively rare type of renal cell carcinoma (RCC). Since now, most of studies on kidney cancer mainly focus on RCC, there has no investigation to find a robust signature to predict the survival outcome of KIRP patients. In this study, we constructed a competing endogenous RNA (ceRNA) network including 1251 lncRNA-miRNA-mRNA interactions. Eight differentially expressed genes (IGF2BP3, PLK1, LINC00200, NCAPG, CENPF, miR-217, GAS6-As1 and LRRC4) based on TCGA database were screened out. Prognostic signature was established by combining univariate cox regression method and a stepwise regression method, with its predictive value validated by time-dependent receiver operating characteristic (ROC) curves. In conclusion, we identified eight prognostic signatures with its ceRNA networks. Our study provided a global view and systematic dissection on KIRP prognosis biomarkers, and the identified eight genes might be acted as novel important prognostic factors involved in KIRP pathogenesis.